Challenges and opportunities in developing Islamic social finance - Haneef, Mohamed Aslam (2017)
Introduction No one can deny the presence of Islamic economics and especially Islamic Banking and Finance. Since the 1960s, Islamic economics began as a ‘movement’, with ideals and higher goals to improve the condition of the ummah at a time when the ummah was just rising from centuries of slumber. With political independence after WW2, Muslim countries needed to find their own solutions to their development challenges. The mid 1970s saw the first commercial Islamic bank established in Dubai. Soon after, one by one Muslim country and even non-Muslim countries set-up Islamic banks. 40 years later, what began as part of the Islamic economics movement had become an Islamic banking/finance industry. By all quantitative accounts, IBF has made its presence felt in the ummah. Yet, there 2 are still voices of dissatisfaction with the role and contribution of IBF to the well-being of the ummah.